Karakteristik Sifat Fisik dan Kimia Tanah pada Lahan Perkebunan Kelapa Sawit (Elaeis guineensis Jacq.) di Desa Batu Belah, Kabupaten Kampar, Riau - Niken Ellani Patitis; Widya Sinta Mustika (Yayasan Literasi Sains Indonesia, 2025)
Soil characteristics play a crucial role in determining soil fertility status, land capability, and sustainable land management strategies through the assessment of physical, chemical, and biological properties. Land management practices in oil palm plantations directly affect plant growth and productivity as the plantation ages. This study aims to identify and evaluate the physical and chemical properties of soils under different oil palm planting ages. The research was conducted in Batu Belah Village, Kampar Regency, Riau, using three age categories: T1 (1–5 years), T2 (5–10 years), and T3 (>15 years). A survey method and direct field observations were employed to determine soil sampling locations. The physical parameters measured included texture, bulk density (BD), particle density (PD), total pore space (TPS), fiber content, and moisture content. Chemical parameters included N, P, K, organic C, pH, Pb, and Cd. The results showed significant changes in several soil physical and chemical properties with increasing plant age. These findings indicate that the evaluation of soil characteristics can guide the development of appropriate soil management strategies to support sustainable productivity in oil palm plantations.